COMPORTAMIENTO DE LA INSUFICIENCIA CARDÍACA AGUDA EN LA UNIDAD DE CUIDADOS INTENSIVOS DE RIBERALTA, BOLIVIA / Behavior of acute heart failure in the Intensive Care Unit of Riberalta, Bolivia - Vielka González Ferrer; Marilyn Ramírez Méndez; Maguett Alonso Padrón; Wilfredo de J. Machin Cabrera; Fernando Rodríguez González (CorSalud, 2011)
Introduction and Objectives: Heart failure is a majorcause of admission to intensive care units. The objectiveof this research was to describe the behavior ofacute heart failure in the Intensive Care Unit of Riberalta,Bolivia. Method: A cross sectional study was conductedwith 141 patients who were admitted with thisdiagnosis in the period June 2006 - August 2008. Results:The most represented age group was 60 yearsand over (37.6%), while acute coronary syndrome wasthe main precipitating factor (29.8%) and cardiomyopathythe fundamental causal factor (36.2%). The mostcommon clinical presentation was acute decompensation(39.7%) and the highest percentage of patientshad a hospital stay of 7 or more days (64.5%), in whichheart failure was more representative (66%) and living discharged patients were more prevalent (80.9%). The largest proportion of patients received potassium sparing diuretics (90.5%), beta blockers (96.9%) or theassociation of inhibitors of angiotensin convertingenzyme and antagonists of angiotensin II receptorswith one of them (95.2 and 94.1% respectively). Therisk of dying was 54 times higher in patients requiringvasoactive drugs, and 9 times in those using digitalis.Conclusions: Female sex predominated with 60 andmore years. Cardiogenic shock, acute pulmonaryedema and the number of admissions were the maindeterminants of mortality. The use of hormone-blockingdrugs was favorably associated with survival; theopposite happened with the inotropes.